(untitled) (Plant Tissue Culture and Biotechnology, 2021)
This study was carried out to develop an in vitro propagation protocol for two tannia (Xanthosoma sagittifolium (L.) Schott) cultivars (green and purple), using shoot tip explants. Shoots were best initiated on the MS supplemented with 2.0 mg/l BAP. The highest number of shoot per explant (green tannia: 4.56 ± 0.35 purple tannia: 4.83 ± 0.26) was recorded on the MS supplemented with 2.5 mg/l BAP and 0.5 mg/l NAA. The longest shoot (green tannia: 3.92 ± 0.40 cm and purple tannia: 4.36 ± 0.46 cm) was recorded on the MS supplemented with 5.0 mg/l BAP, 1.0 mg/l Kn and 0.5 mg/l NAA. The highest number of roots per shoot (green tannia: 6.00 ± 0.74 and purple tannia: 5.83 ± 0.49) was obtained on the medium containing 2.0 mg/l IBA. The results of this study showed that tannia could efficiently be propagated in vitro by incorporating appropriate concentration of PGRs. Plant Tissue Cult. & Biotech. 31(1): 25-34, 2021 (June)